STABILNOST SLOVENSKEGA BANČNEGA SISTEMA IN VLOGA BANKE SLOVENIJE - Kušnik, Davorin (D. Kušnik, 2011)
Diplomski seminar združuje tematiko sodobne in vse bolj nujne finančne stabilnosti znotraj slovenskega nacionalnega okvira, vpliv in vlogo Banke Slovenije ter posledice zadnje svetovne finančne krize. Zgodovina ekonomske znanosti vseskozi nakazuje dejstvo, da gospodarska rast nikoli ni linearna in razvoj nikoli ni konstanten. Obdobju prosperitete skoraj zagotovo sledi obdobje recesije in obratno. V postavljanju ogrodja za zdrav in predvsem stabilen finančni sistem neke države, morajo največ postoriti državni subjetki sami. Ključno je sodelovanje tako na nacionalni kot tudi mednarodni ravni, ki mora v procesu vzdrževanja stabilnosti finančnega sistema iskati poti naprednih izboljšav, zaščititi končne odjemalce finančih proizvodov in v kočni fazi doseganje cilja stabilnosti finančnega sistema. As the history of economic science shows, the expansion of economy was never linear and growth was never constant. Every economy enjoys a financial prosperity and development for a period of time, but because of the cycling nature of process, it will be followed by a period of regression which results could resolve in financial crisis. Again, afterwards the depression, the same process is extracting in state of prosperity, the only question remain is how fast the extraction will be. We can definitely say processes within national frames are subordinated on all involved subjects, their motives and interests but mainly it is the state which regulates and limits activities throughout legislation regulation, carried out by supervision institutions. To build a healthy and stabile national financial system it is necessary that national subjects themselves are fully involved and responsible. Cooperation on an international level is just an additional task of states financial politics, providing help with their know-how knowledge, experiences and practically tested solutions in contribution to reach constant achievement, protection of financial consumers and forming overall financial stability.